Portraits of babies & children - Civardi, Giovanni (Tunbridge Wells, Kent Search Press, 2017)
For admirers of the world renowned life-drawer, and for those who have struggled to capture the ever-changing features of younger faces, this book by Giovanni Civardi will teach and guide the reader to observe, evaluate and, finally, design children's heads and expressions. Using his expert knowledge in anatomy and proportion, and providing a number of tips and techniques on sketching and the different materials
Drawing
1
Keywords: Children in art; Drawing; Portraits